Experimental investigation of scavenging in two-stroke engines using continuous CO2 sampling. (June 2022) - Bajwa, Abdullah U; Patterson, Mark; Jacobs, Timothy J
In internal combustion engines, the chemical composition of the trapped fuel-air-residual gas mixture controls the nature of combustion, which, in turn, determines the characteristics of the ensuing emissions and work production processes. Therefore, knowledge of the trapped mixture's composition is critical for reliably predicting and controlling engine performance, emissions, and efficiency. A good index of the overall trapped mixture composition is the trapped equivalence ratio. Unfortunately, in two-stroke engines, it is unfeasible to accurately determine the trapped equivalence ratio using traditional intake flow measurements and exhaust emissions data. This limitation arises from the simultaneous occurrence of intake and exhaust processes in two-stroke engines, which causes: (1) exhaust emissions to be diluted by excess fresh air that was supplied for achieving effective gas exchange, that is trapping inefficiencies and (2) a significant fraction of combustion products to stay back in the cylinder as residual gas, that is scavenging inefficiencies. The current paper presents an experimental study carried out on a cross-scavenged, lean-burn, natural-gas, two-stroke engine to characterize its scavenging performance, thus paving the way for trapped equivalence ratio computation. CO2 is used as a tracer for combustion products, and its concentration is tracked in the combustion chamber and exhaust manifold on a crank-angle-resolved basis using high-speed nondispersive infrared sensors. The changes in cylinder CO2 concentration before and after gas exchange are used to determine the trapped residual fraction and various features of the exhaust CO2 "wave" are used to explain the temporal progression of the gas exchange process. The presented results show the effects of changes in engine operation (speed, load, and spark-timing) on the engine's scavenging efficiency. Speed and load changes are found to have the most pronounced effects, which result from changes in port open duration and phasing of reflected waves in the exhaust.